(untitled) (Revista Contexto & Saúde, 2026)
Objective: To assess pharmacists’ educational needs in asthma care in order to inform the design of a nationwide educational strategy. Methods: A descriptive, quantitative study was conducted using an online survey with convenience sampling. The questionnaire was disseminated through the Federal Pharmacy Council’s Instagram® account and included open- and closed-ended items addressing professional practice, patient questions and beliefs, and training needs. Data were analyzed descriptively, with thematic coding of qualitative responses. Results: A total of 576 responses were obtained from pharmacists working across different regions of Brazil. Most reported providing care to individuals with asthma (94.7%). Overall, 89.1% identified at least one educational need, most commonly related to treatment and clinical protocols (32.7%) and the use of inhalation devices (23.2%). The most frequent patient questions concerned correct inhaler use (60.7%) and understanding the chronic nature of the disease (20.7%). Colloquial expressions (e.g., chiado, piado) and beliefs related to the use of teas, homemade remedies, and traditional practices were also reported, with implications for treatment adherence. Conclusion: Pharmacists’ educational needs closely mirror patients’ most common questions, highlighting the importance of training programs that address the sociocultural context of care and support the development of practical and communication skills for asthma management.